Spatial distribution of ticks and tick-borne pathogens in central Hokkaido, Japan and associated ecological factors revealed by intensive short-term survey in 2024 - Mebuki Ito; Yuma Ohari; Mai Kishimoto; Keita Matsuno (PLoS ONE, 2026)
Tick-borne pathogens are transmitted by tick bites to cause infectious diseases in humans and domestic animals. To anticipate tick-borne disease occurrence, a high resolution understanding of infection risk distribution and its ecological drivers is needed. We aimed to map the spatial distribution of ticks and pathogen-infected ticks in central Hokkaido, Japan. Adult and nymphal ticks were collected with constant effort at 171 sites from 13 May to 26 June 2024, followed by screening tick-borne pathogens and ecological niche modeling. A total of 9,908 ticks were collected and the endemic tick-borne pathogens (i.e., tick-borne encephalitis virus, Yezo virus, Beiji nairovirus, Lyme disease group borreliae, and relapsing fever group borreliae) were primarily detected in Ixodes spp. ticks. Potential suitable habitats of the ticks and pathogens were predicted using the presence/absence data based on tick collection and pathogen detection. The models achieved acceptable predictive performance (median AUC = 0.83 and median TSS = 0.59 in leave-one-out cross‑validation). Ixodes persulcatus and Ixodes ovatus were identified as the primary ticks for determining the distributions of all the pathogens. Besides, the predicted suitable habitats differed among pathogen and tick species. Among the environmental variables considered for modeling, snow depth appeared to significantly contribute to the distribution differences between ticks and pathogens. The findings of this study expand our understanding of the spatial risk distribution of tick-borne pathogen infections and its ecological context.